1998
DOI: 10.1128/jvi.72.2.1334-1344.1998
|View full text |Cite
|
Sign up to set email alerts
|

Differential Tropism and Chemokine Receptor Expression of Human Immunodeficiency Virus Type 1 in Neonatal Monocytes, Monocyte-Derived Macrophages, and Placental Macrophages

Abstract: Laboratory-adapted (LA) macrophage-tropic (M-tropic) human immunodeficiency virus type 1 (HIV-1) isolates (e.g., HIV-1Ba-L) and low-passage primary (PR) isolates differed markedly in tropism for syngeneic neonatal monocytes, monocyte-derived macrophages (MDMs), and placental macrophages (PMs). Newly adherent neonatal monocytes and cultured PMs were highly refractory to infection with PR HIV-1 isolates yet were permissive for LA M-tropic isolates. Day 4 MDMs were also permissive for LA M-tropic isolates and add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(39 citation statements)
references
References 78 publications
4
35
0
Order By: Relevance
“…CCR3 receptor expression is not detected on adult monocytes, concordant with lack of CCR3 mRNA [38]. Both adult [48][49][50] and neonatal [46] monocytes express CD4.…”
Section: Monocytesmentioning
confidence: 86%
See 1 more Smart Citation
“…CCR3 receptor expression is not detected on adult monocytes, concordant with lack of CCR3 mRNA [38]. Both adult [48][49][50] and neonatal [46] monocytes express CD4.…”
Section: Monocytesmentioning
confidence: 86%
“…Whilst CCR5 transcripts are readily detected in freshly isolated monocytes, CCR5 surface expression is not detected on these cells [38,44,45]. Following 24 h in culture, surface CCR5 is observed on monocytes from adult but not neonatal donors [38,46]. The surface expression of CXCR4 and CCR2b is high on freshly isolated monocytes [38,47].…”
Section: Monocytesmentioning
confidence: 99%
“…CCR5-transfected HeLa-CD4 cells could be infected by R5 HIV-1 isolates even if those cells had small amounts of CD4 [61], and the susceptibility of maturing monocytes to HIV-1 infection correlated with CCR5 expression [65]. Furthermore, the differences between neonatal and adult monocytes in susceptibility to primary clinical isolates may be related to the level of CCR5 expression [66]. However, the CD4 and CCR5 concentration requirements for efficient infections by R5 HIV-1 are interdependent: cells with a large amount of CD4 required only a trace amount of CCR5 for maximal susceptibility to infection by diverse isolates of R5 HIV-1, whereas cells with a low amount of CD4 required a much larger amount of CCR5 for infection [63].…”
Section: Cada a Specific Down-modulator Of Cd4mentioning
confidence: 98%
“…Despite this susceptibility, our laboratory and others [4 -8] have demonstrated that HIV-1 production by PM is significantly lower than that observed in MDM. PM express lower levels of the CD4, CXCR4, and CCR5 receptors than do MDM [9,10]. LPS-stimulated PM produce lower levels of proinflammatory cytokines than do LPS-stimulated MDM, but there is no correlation of cytokine secretion with HIV-1 infection [8].…”
Section: Introductionmentioning
confidence: 99%